Environmental protection of international watercourses under international law - McIntyre, Owen (Ashgate, 2007)
McIntyre's work explains the legal means by which requirements of environmental protection influence the determination of a reasonable and equitable regime for allocating rights to riparian states to utilize shared freshwater resources.
Keywords: International rivers; Water rights (International law); Water : Pollution : Law and legislation; Water resources development : Law and legislation; Liability for water pollution damages